Analisis Potensi Kearifan Lokal sebagai Daya Tarik Utama Desa Wisata Kampuang Minang Nagari Sumpu Kabupaten Tanah Datar, Sumatera Barat - Christin Eva; Muhammad Alfi; Regita Asiah Azzarah; Dini Afrilia; Ridha Suyatmika Nainggolan; Wafiq Ariska; Rosni Rosni; Mulhady Putra (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Kampuang Minang Tourism Village in Nagari Sumpur, Tanah Datar Regency, West Sumatra, is a culture-based tourism village that highlights the potential of local wisdom as the main attraction. This research aims to analyze this potential and identify challenges and opportunities in its preservation. The research uses a qualitative approach with a case study method, through in-depth interviews, observations, and documentation. The results show that cultural elements such as rumah gadang, bajamba meal processions, and traditional arts have been successfully packaged into an authentic tourism experience through the concept of family homestay. However, the development of tourist villages faces obstacles such as limited infrastructure, low participation of the younger generation, and perceptions of injustice in the management of Pokdarwis.